Establishing the linkages of human resource development with inclusive growth - Tullao, Tereso S., Jr. (Animo Repository, 2015)
This study aims to establish the linkages between human capital and human resource development, and inclusive growth in an economy. Various studies have suggested that education, training, and human resource development, in general, raise the productivity of workers through the transmission of knowledge, skills, and competencies, which then increase the earning capacity of an individual. Because of the link between education and earning capacity, improving education will bring about inclusive growth, as these same educated individuals enhance their employment opportunities, improve their income, and pursue entrepreneurial options. The state of education in the Philippines, as well as in the member-economies of the Asia-Pacific Economic Cooperation (APEC), was analyzed in terms of four dimensions: quality, relevance, access and equity, and efficiency and effectiveness. Likewise, options for the development of human resources in the Philippines and lessons learnt from best practices in APEC economies were categorized according to these four dimensions. Lastly, this study enumerates several actionable recommendations on how member-economies in the Asia-Pacific region can cooperate to bridge their human resource gaps and ultimately attain inclusive growth.